Investigation of In0.5Ga0.5As/GaAs quantum dots - Atici, Y; Hovesepain, A; Cherns, D; Polimeni, A; Henini, M; Eaves, L (Iop Publishing Ltd, 1998)
[Abstract Not Available]
14th International Congress on Electron Microscopy -- AUG 31-SEP 04, 1998 -- CANCUN, MEXICO